Testing and Evaluation of the Oil Absorption Characteristics of Cotton Fibers. Issue 16 (28th November 2022) - Cao, Shengbin; Sun, Xiangling; Li, Yuanyuan; Xu, Guangbiao; Yang, Junwei
ABSTRACT: The wetting property to different oil of cotton fibers which come from different regions of China was studied. The surface adsorption characteristics of cotton fibers were characterized. It is found that the oleophilic and hydrophobic properties of all the raw cotton fibers are fantastic and the average static contact angle of cotton fibers to water is 135.36°, but it is less than 51° to different oil such as engine oil, waste oil and salad oil. In the dynamic spreading process, the droplets of water formed on the surface of cotton fibers and the contact angles of all the cotton fibers to water is not changing with time while the oil liquids were quickly and completely spread out almost in 2000  ms . The speed of spreading is closely relevant with the viscosity of oil and the higher oil viscosity, the slower wetting velocity. The contact angles of cotton fibers come from different regions to the same oil liquid had little changes, thus the adsorption velocity difference of cotton fibers to engine oil, waste oil and salad oil was not significant, respectively.